CORRELATION OF 75G ORAL LUCOSE TOLERANCE TEST (OGTT) VALUES WITH PREGNANCY OUTCOMES IN A TERTIARY CARE UNIT - Jayarathne, R N; wijeyaratne, C N; Dodampahala, S H; Lankeshwara, D; Randeniya, C (The Sri Lanka College of Obstetricians and Gynaecologists, 2007)
BACKGROUND:Gestational diabetes mellitus (GDM) is a common problem in Sri Lankan tertiary care. Accurate diagnosis b<, OGTT is important. OBJECTIVE:To assess the correlation of OGTT values with pregnancy management and outcome METHOD - DESIGN:Retrospective observational study RESULTS:83 women screened by OGTT in mid trimester during 2007 were recruited postpartum. Of them 25 1~had normal and 36 had abnormal glucose tolerance (20 - frank diabetes; 16 impaired glucose tolerance (IGT)), WHO recommendations 1999; 22 others had 'unusual OGTT' -2 hour value >140 mg/dl and low 1 hour value. Mean age was 31.4 t 5.3 years. Median parity 2; mean number of children 1 with 17 primigravida. OGTT had been performed at average gestational age 23.2 t 6.7 weeks. Mean 111 and 2h OGTT values (mg/dl) were: normal -152.7 t 6.7 and 113 ñ 17.9, frank diabetes-201ñ28.5 and 189t21.6, IGT - 179ñ22.6 and 149ñ11.4 and 'unusual OGTT' - 118.7ñ16.4 and 14718.6 respectively. Maternal glycaemia by Blood Sugar Series at average gestational age 26.9ñ6.7 weeks - mean pre meal and mean 2 hour post meal blood glucose (mg/dl): normal 96.8ñ11.4 and 101.9ñ17.2 and 'unusual OGTT' 87.2ñ14.3 and 99.912 respectively. PREGNANCY OUTCOME:Unusual OGTT'- none required insulin; 14 (63.6 percent) had vaginal delivery. 7 LSCS for previous section and one assisted deliver, with mean birth weight